The atp operon: nucleotide sequence of the genes for the gamma, beta, and epsilon subunits of Escherichia coli ATP synthase. - Saraste, M (1981)
The nucleotide sequence of the promoter distal region of the atp (or unc) operon of Escherichia coli has been determined. It encodes the gamma, beta and epsilon subunits of the ATP-synthase complex and includes a noncoding sequence in which transcription of the operon probably terminates. This work completes the nucleotide sequence of the operon which contains nine genes: eight encode structural proteins of the ATP-synthase complex; a ninth, the first in the operon, may be a pilot for assembly. The genes for the alpha and beta subunits have evolved from a common ancestor.